Pemberdayaan Industri Pengerajin Bambu di Dusun Gunung Mijil untuk Meningkatkan Penjualan melalui Pemasaran Digital - Wawan Sadtyo Nugroho; Abizart Wicaksonando; Vikri Putra Nur Hanan; Naufal Rizky Kurniawan; Agil Zamzam Kurniawan (Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2023)
The purpose of this service is to provide new understanding and insight to Bamboo Craftsmen that digitalized marketing and good branding will be able to expand consumers of handicraft products being sold and also retain existing consumers. The method used to achieve this goal is to carry out five stages of service activities, namely socialization, training, practice, mentoring and evaluation. The results achieved are additional insight, understanding and knowledge of bamboo craftsmen in operating social media as a means of digital marketing to sell their products. In addition, this digitalized marketing is expected to have an economic impact on bamboo craftsmen in Gunung Mijil Hamlet, Kebonsari Village.